PROSPECTS FOR THE DEVELOPMENT OF DUAL EDUCATION IN THE PREPARATION OF HIGHLY QUALIFIED SPECIALISTS IN RAILWAY TRANSPORT - Панченко, Сергій; Приходько, Сергій; Каменєв, Олександр; Лапко, Антон; Василега, Людмила; Терещенко, Юрій (New Collegium, 2020)
The article considers the main problems and prospects of introducing dual training technologies in higher education institutions that specialize in the preparation of bachelors and masters for the needs of railway trans- port. During the study, the main problems that impede the quality training of highly qualified specialists for the transport industry are analyzed. it is established that the use of dual education can become the main set of means measures that can reduce the gap between the theoretical and practical components of educational programs. The basic possibilities for the phased implementation of dual technologies in the educational process are examined using the example of the Ukrainian State University of Railway Transport. it has been established that the main reserves for the allocation of the budget of the academic load for the implementation of these technologies are independent work of students, course and diploma design, as well as a laboratory workshop in special disciplines. Depending on the subject area of training specialists in dual technology, two main technologies of dual training are proposed as part of the implementation of individual educational paths — project-dual and operational-dual. Based on the example of phased preparation of a bachelor and then a master in the specialty "Automation and Computer-integrated Technologies", a diagram of a gradual increase in the volume of industrial training of students, from the first to the final courses, is proposed. Finally, the main organizational measures that the stakeholders of the dual process have to carry out in order to properly implement this form of training in the educational process of transport educational institutions are developed and proposed. As a result of their implementation, a substantial increase in the level of professional adaptation of graduates during subsequent labor activities within the framework of acquired specialties and qualifications is expected. Key words: dual education; railway transport; practical training; organization of employers.